Dengue prevention. Everyone's task - Pérez Hernández, Fabián; Morales Arrastía, María Caridad; Azcuy García, Ivany; Martín Sánchez, Aned; Olivera Valdés, Aymé (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Introduction: Dengue continues to be a public health problem in the region of the Americas, despite efforts by Member States to contain it and mitigate the impact of epidemics.Objective: to carry out Dengue prevention actions with an intersectoral and community approach.Methods: an action research was carried out in a community of the Raúl Sánchez Rodríguez university polyclinic, the universe was composed of 134 families, a sample of 82 was selected by non-probabilistic sampling. Theoretical methods were used, observation, surveys, to reach a diagnosis and then present an action plan with activities for the prevention and control of Dengue. Descriptive statistics were used, given in absolute and relative numbers.Results: mosquito breeding sites, micro dumps, poor sanitary culture related to environmental hygiene, lack of knowledge of the autofocal, not attending in time the symptoms and warning signs were identified. A plan of activities was drawn up with community and intersectoral participation led by the basic health team with a view to intensifying efforts to eliminate mosquito breeding sites and protect against bites, prepare health services for early diagnosis and timely clinical management, and educate the population about the symptoms of dengue so that they seek medical attention immediately.Conclusions: strengthening surveillance, early diagnosis and timely treatment contributes to saving thousands of lives, and dealing with dengue is the task of all sectors of society.